Karakter pengunjung dan radius layanan taman kota:studi kasus Taman Puputan Badung I Gusti Ngurah Made Agung, Denpasar - Kohdrata, Naniek; Krisnandika, Anak Agung Keswari; Semarajaya, Cokorda Gede Alit (Jurnal Arsitektur Lansekap; Vol.6, No.2, Oktober 2020DO - 10.24843/JAL.2020.v06.i02.p13, 2020)
City Park Service Distance: Case Study of Puputan Badung I Gusti Ngurah Made Agung Denpasar Park. This research is a preliminary work on finding out how a park has been functioned as a public facility to a city. It is aimed to find out Lapangan Puputan Badung service distance range as one of Denpasar city parks. Moreover, it is also to find out the characteristic uses of the park by its users. This case study uses a survey research method. Sample of respondents are chosen using accidental sampling technique with questionnaire as media of data collection. Research findings are analyzed spatially and descriptively as well. Result shows that most samples live within 5 km range from the park. The park has been used mostly for recreation and exercises. People within productive age have been dominated the use of the park. Duration people spend in the park is between 1 – 2 hours, however there is an interesting finding that 15% samples say that they spend 3 – 4 hours in the park. There is also a strong tendency that people uses the park as a group, meaning they might be there with family, relatives, or friends. More than 50% of user respondents are the park frequent visitors. As conclusion, it can be stated that Lapangan Puputan Badung function the best to serve the dwellers within 5 km radius.